THE EFFECT OF CORPORATE IMAGE ON BRAND AWARENESS AND BRANG ATTITUDE - Didit Darmawan (Universitas Islam Balitar, 2019)
Various advancements and dynamics in the business world led to rapid developments in various industries. Corporate image is the main provision to survive in industrial competition. With the existence of a good corporate image, it is expected to increase brand awareness and brand attitude of the products circulating in the market. This study will examine the effect of corporate image on brand awareness and brand attitude. This study involved 100 respondents using an analytical tool in the form of simple linear regression with proof through t test. The results of the study show that the corporate's image significantly influences brand awareness and brand attitude.